2018
DOI: 10.1002/ase.1840
|View full text |Cite
|
Sign up to set email alerts
|

Is This Mine to Keep? Three‐dimensional Printing Enables Active, Personalized Learning in Anatomy

Abstract: Understanding orbital anatomy is important for optometry students, but the learning resources available are often fragile, expensive, and accessible only during scheduled classes. Drawing on a constructivist, personalized approach to learning, this study investigated students' perceptions of an alternative learning resource: a three-dimensional (3D) printed model used in an active learning task. A human skull was three-dimensionally scanned and used to produce a 3D printed model for each student. Students acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 49 publications
(68 reference statements)
2
43
0
Order By: Relevance
“…The findings of this study demonstrate not only a high engagement with the learning activity and content, but also appears to have added value to the overall learning experience, through active and deep learning. Furthermore, the focus group findings mirror that of Backhouse et al (2019), who found that a cohort of optometry using their own 3DP skull models to study anatomy strongly resonated with the ownership and personalized aspects of the models. Hence, the findings suggest that the concept of ownership is important in building student engagement and that these concepts may have a downstream effect on both student learning strategies and perceived course educational value.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The findings of this study demonstrate not only a high engagement with the learning activity and content, but also appears to have added value to the overall learning experience, through active and deep learning. Furthermore, the focus group findings mirror that of Backhouse et al (2019), who found that a cohort of optometry using their own 3DP skull models to study anatomy strongly resonated with the ownership and personalized aspects of the models. Hence, the findings suggest that the concept of ownership is important in building student engagement and that these concepts may have a downstream effect on both student learning strategies and perceived course educational value.…”
Section: Discussionsupporting
confidence: 71%
“…Literature also suggests that that the quality and detail of the 3DP model can aid in achieving higher degrees of successful learning outcomes (Kong et al, 2016). More recently, it has been shown that personal 3DP anatomical models can be used effectively to augment both the curriculum and more traditional laboratory‐based learning approaches (Mogali et al, 2018; Smith et al, 2018; Backhouse et al, 2019). Despite the widespread adoption of 3DP anatomical models into medical and surgical education and training (Baskaran et al, 2016; Fasel et al, 2016; Lim, et al, 2016), there is little research that explores the effectiveness of their use in other health education disciplines (Azer and Azer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported a growing concern over the loss of anatomy knowledge throughout medical programs (Bhangu et al, ; Jurjus et al, ; Doomernik et al, ; Easteal and Perry, ; Norris et al, ) and allied‐health disciplines such as physical therapy (Anderson and Conley, ), kinesiology (Wagner, ), chiropractic (Strkalj et al, ), veterinary science (Wade and Walker, ), physician assistant (Keim Janssen et al, ) speech‐language pathology (Barros et al, ), optometry (Backhouse et al, ), podiatry (Díaz‐Mancha et al, ), and nursing (McVicar et al, , ; Booth et al, ; Alt‐Gehrman, ). These studies suggest that there is great difficulty not only in transferring fundamental anatomy knowledge to theory/clinical application but also a loss of that knowledge over time (Bhangu et al, ; Brunk et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the knowledge retention studies cited above were focused on single specific organ systems (Díaz‐Mancha et al, ) or regional gross anatomy (Starkalj et al, ; Jurjus et al, ; Brunk et al, ; Doomernik et al, ) and were focused on either medical (Bhangu et al, ; Finnerty et al, ; Jurjus et al, ; Doomernik et al, ; Easteal and Perry, ; Norris et al, ) or allied health students (Fiebert and Waggoner, ; Strkalj et al, ; Keim Janssen et al, ; Barros et al, ; Backhouse et al, ). However, for nursing education worldwide, retention of anatomy knowledge has not yet been studied as extensively as for medical (Jurjus, et al, ; Doomernik et al, ) and allied‐health students (Wade and Walker, ; Strkalj et al, ; Keim Janssen et al, ; Meyer et al, ; Barros et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation